LEADERSHIP AND NURSING CARE MANAGEMENT - HUBER, Diane (W.B Sounders Comp, 2000)
Uniquely organized around the AONE competencies, this trusted resource gives you an easy-to-understand, in-depth look at today’s most prevalent nursing leadership and management topics. Coverage features the most up-to-date, research-based blend of practice and theory related to topics such as: the nursing professional's role in law and ethics, staffing and scheduling, delegation, cultural considerations, care management, human resources, outcomes management, safe work environments, preventing employee injury, and time and stress management.